1999
DOI: 10.1161/01.cir.100.21.2131
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Sensitive Dysregulated AT1 Receptor Function and Density in Hypercholesterolemic Men

Abstract: Hypercholesterolemia induces AT1 receptor overexpression and enhances biological effects of angiotensin II in men. These findings provide novel insights into the pathogenesis of hypertension and atherosclerosis and may initiate rational and new therapeutic concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
1
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(249 citation statements)
references
References 21 publications
10
227
1
11
Order By: Relevance
“…We found that the blood pressure response to noradrenaline was unchanged, which agrees with Nickenig and colleagues 4 who found no significant difference in the response to infused Figure 1 Effect of various cholesterol lowering treatments on total cholesterol and baroreflex sensitivity (BRS) in hypercholesterolaemic men. *p < 0.05 for total cholesterol and BRS.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the blood pressure response to noradrenaline was unchanged, which agrees with Nickenig and colleagues 4 who found no significant difference in the response to infused Figure 1 Effect of various cholesterol lowering treatments on total cholesterol and baroreflex sensitivity (BRS) in hypercholesterolaemic men. *p < 0.05 for total cholesterol and BRS.…”
Section: Resultssupporting
confidence: 90%
“…Noradrenaline was used instead of phenylephrine to test the baroreflex as it was felt to be more physiological than phenylephrine and because it had been used in a landmark study by Nickenig. 4 Supine blood pressure and heart rate were measured in triplicate at the start for baseline value and every five minutes thereafter during the study (Dinamap critical signs monitor 1846, Critikon, Tampa, Florida, USA). The infusion was stopped if the systolic blood pressure rose by 50 mm Hg.…”
Section: Methodsmentioning
confidence: 99%
“…This also agrees with the finding that statin reversed the increased expression of AT1 and the augmented BP response to angiotensin II in hypercholesterolemic men. 29 Thus, it is speculated that both hypercholesterolemia and hypertension would be closely linked to augmented AT1 stimulation in this model. Although further mechanisms remain unknown, our findings imply that the combination of OLM and PRA will clinically benefit lipid and BP control per se in patients with metabolic syndrome.…”
Section: Lipid-lowering and Antihypertensive Effectsmentioning
confidence: 88%
“…44 Statins downregulate AT1R expression in platelets and vascular smooth muscle cells. 45,46 Thus, simvastatin may prevent SAD-induced aggravation of hypertensive cardiac hypertrophy, at least in part, by inhibiting the angiotensin II-mediated mechanism. This issue should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%